Using Heading date 1 preponderant alleles from indica cultivars to breed high-yield, high-quality japonica rice varieties for cultivation in south China - Leng, Yujia; Gao, Yihong; Chen, Long; Yang, Yaolong; Huang, Lichao; Dai, Liping; Ren, Deyong; Xu, Qiankun; Zhang, Ya; Ponce, Kimberly; Hu, Jiang; Shen, Lan; et al. (Wiley, 2020)
Heading date 1 (Hd1) is an important gene for the regulation of flowering in rice, but its variation in major cultivated rice varieties, and the effect of this variation on yield and quality, remains unknown. In this study, we selected 123 major rice varieties cultivated in China from 1936 to 2009 to analyse the relationship between the Hd1 alleles and yield‐related traits. Among these varieties, 19 haplotypes were detected in Hd1, including two major haplotypes (H8 and H13) in the japonica group and three major haplotypes (H14, H15 and H16) in the indica group. Analysis of allele frequencies showed that the secondary branch number was the major aimed for Chinese indica breeding. In the five major haplotypes, SNP316(C‐T) was the only difference between the two major japonica haplotypes, and SNP495(C‐G) and SNP614(G‐A) are the major SNPs in the three indica haplotypes. Association analysis showed that H16 is the most preponderant allele in modern cultivated Chinese indica varieties. Backcrossing this allele into the japonica variety Chunjiang06 improved yield without decreasing grain quality. Therefore, our analysis offers a new strategy for utilizing these preponderant alleles to improve yield and quality of japonica varieties for cultivation in the southern areas of China.